Disabled Entrepreneurs: Challenges in Utilizing Digital Marketing in MSMEs - Ikhsan, Rudfiando Ikhsana; Syah, Muhammad Fahmi Johan; Custilas, Anesito (Jurnal Ilmu Sosial Mamangan, 2024)
People with disabilities have long experienced discrimination, resulting in the unfulfillment of their rights. Different physical or non-physical conditions place disabled groups in the chain of poverty, socially, politically, and economically. This research aims to describe an entrepreneur with a disability in facing the challenges of utilizing digital marketing in MSMEs. The research respondent is an entrepreneur with a disability in the health drink sector, specifically a visually impaired individual in Surakarta. This study employs a case study research design with a qualitative approach. Data is collected through participant observation, semi-structured interviews, and documentation. The validity of the data is tested using an interactive model, and the data analysis model employed is the interactive model by Miles, Huberman, and Saldana. The results of this research indicate an increase in knowledge and skills among entrepreneurs with disabilities to confront challenges in utilizing digital marketing. Additionally, disabled entrepreneurs experience enhanced skills such as critical thinking, independence, and problem-solving when facing the challenges of digital marketing in MSMEs.